Process gap analysis and modelling in enterprise systems. (31st August 2005) - Lorenzo, Oswaldo; Diaz, Angel
This paper proposes an empirically-supported framework for process gap analysis and modelling of enterprise systems (ES), both critical and often overlooked activities in ES implementations. In doing so, the paper seeks to give some insight into how to tackle the reconciliation of business process requirements with ES functionality. The four-step method involves: current situation analysis; business process improvements and requirements; gap analysis; to-be processes, which are the trigger for the definition of organisational adaptation and system configuration and tailoring agendas. Outputs of the methodology are: an interdependent set of organisational and system-proposed changes and tailoring; feedback loops to the vendors of ES and to the strategy of the firm. In-depth multiple case studies and an extensive literature review provide methodological support for the model. For practitioners, this study provides useful insights into one of the possible reasons for organisations' becoming frustrated with ES implementation processes.